Modification of screen-printed electrodes with Prussian Blue (PB) and enzyme for diabetes control in sweat: Preliminary feasibility study : Modification of screen-printed electrodes with Prussian Blue (PB) and enzyme for diabetes control in sweat: Preliminary feasibility study - Beltrán-Gastélum, Mara; Gutiérrez-Gutiérrez, Reyna; Godínez-Dávalos, Bruno U.; Salazar-Gastélum, Moisés Israel; Cárdenas-Valdez, José Ricardo; Pérez-Sicairos, Sergio (Revista Mexicana de Ingenieria Biomedica, 2026)
The prevalence of diabetes in Mexico has increased considerably over the past 20 years, thus increasing the need for the development of non-invasive and reliable glucose monitoring platforms. The present research focus on the development and evaluation of a novel non-invasive glucose monitor for the quantification of glucose levels in sweat. This platform is based on the use of screen-printed electrodes modified with a Prussian Blue (PB) electrochemical mediator and the glucose oxidase (GOx) enzyme to provide glucose specificity. Additionally, we present the design of a portable electronic device for generating the input signal and processing the analyte output signals. The system was evaluated in a 0.1 M phosphate buffered saline (PBS) solution supplemented with different physiologically relevant glucose concentrations. The results demonstrated that the PB mediator plays a key role in the detection of glucose, since the control electrode modified with the enzyme but lacking the PB mediator did not show trend, while the electrode modified with PB and enzyme showed a good correlation coefficient with analytical sensitivity of 0.0008 mA μM-1. This finding could revolutionize the field of glucose monitoring, facilitating more accessible and less invasive health technologies.